A Critical Discourse Analysis of Song "Easy on Me" by Adele - Putu Sukma Dewi (Linguistics Initiative, 2022)
The purpose of this research is to analyze how the role or attitude of the author towards a song that was created by examining the effect, judgment, and appreciation. The researcher used descriptive qualitative method by using three analytical processes proposed by Fairclough's CDA model. The data from this research are the lyrics of Adele's song entitled "Easy on Me". The findings show that Adele describes her feelings in this song explicitly by using a figure of speech. In her song, Adele conveys the effect of how worried and devastated she is when faced with the problem of her divorce. In the aspect of assessment, Adele admires nature through her own point of view, so that some of her song lyrics are interpreted using the beauty and serenity of nature. Based on appreciation, Adele assesses that divorce or separation in a relationship is the end of her journey, so she wants to give up and surrender.